CeO2 induced dispersive distribution of TiB2 particles in in situ TiB2/Al composite. (July 2014) - Xue, J.; Han, Y. F.; Lei, J. B.; Wang, J.; Sun, B. D.
Abstract : The roles of CeO2 additive during preparation of in situ TiB2 /Al composite, alleviating particle settlement in composite melt and significantly improving particle dispersion in final microstructure, are studied in this paper. It is evidenced that the CeO2 additive reacts with Al melts to release Ce solute into the melts, and the released surface active Ce is absorbed in the Al/TiB2 interfaces without any other reaction products. First principles calculations show that the interfacial energy of Al/TiB2 interfaces is reduced owing to the presence of Ce in Al/TiB2 interfacial area. Therefore, the wettability of molten Al on TiB2 surface is increased and the dispersion of TiB2 particles in Al matrix is eventually improved.